2019
DOI: 10.1186/s12889-019-8010-8
|View full text |Cite
|
Sign up to set email alerts
|

Current prevalence pattern of tobacco smoking in Nigeria: a systematic review and meta-analysis

Abstract: BackgroundNational smoking cessation strategies in Nigeria are hindered by lack of up-to-date epidemiologic data. We aimed to estimate prevalence of tobacco smoking in Nigeria to guide relevant interventions.MethodsWe conducted systematic search of publicly available evidence from 1990 through 2018. A random-effects meta-analysis and meta-regression epidemiologic model were employed to determine prevalence and number of smokers in Nigeria in 1995 and 2015.ResultsAcross 64 studies (n = 54,755), the pooled crude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 59 publications
2
55
1
Order By: Relevance
“…All the smokers were males as consistent with what obtains in Nigeria where tobacco use is predominantly among males. [ 26 ] In contrast, in a cross-sectional study conducted among PLWHIV in Jos, Nigeria, the prevalence of those who had or were currently smoking cigarette was reported to be 25.7%. [ 27 ] The low prevalence of tobacco use in this study may be attributed to the fact that there was a greater proportion of females in the study who have been documented to be less likely to smoke, unlike males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the smokers were males as consistent with what obtains in Nigeria where tobacco use is predominantly among males. [ 26 ] In contrast, in a cross-sectional study conducted among PLWHIV in Jos, Nigeria, the prevalence of those who had or were currently smoking cigarette was reported to be 25.7%. [ 27 ] The low prevalence of tobacco use in this study may be attributed to the fact that there was a greater proportion of females in the study who have been documented to be less likely to smoke, unlike males.…”
Section: Discussionmentioning
confidence: 99%
“…[ 27 ] The low prevalence of tobacco use in this study may be attributed to the fact that there was a greater proportion of females in the study who have been documented to be less likely to smoke, unlike males. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…This study indicated considerable variation across geographical areas, from 5.4% in North-west to 32.1% in North-East. [ 26 ] The range across Iran is also quite wide. A meta-analysis conducted by Moosazadeh in 2013 found that smoking prevalence was estimated to be 22.9 (20.6–25.2) in men and 0.6 (0.3–0.9) in women.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional studies examining tobacco use show 2–4-fold higher tobacco utilization among PWH compared to the general population ( Table 1 ) [ 20 ]. For example, in Nigeria, 10% of the general population smoke compared to 22% of PWH [ 8 , 21 ]. In South Africa, the smoking prevalence is 18% in the general population but 25% among PWH [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%